KHARISMA KEPEMIMPINAN TOKOH AGAMA PADA MASYARAKAT BATAK TOBA DAN RELEVANSINYA TERHADAP PERKEMBANGAN GEREJA DI TAPANULI BAHAGIAN UTARA (ANALISIS SOSIOLOGIS) - Harisan Boni Firmando (Studia Sosia Religia, 2021)
Abstract            Striving for interaction in society is well-established in order to create social harmony. The realization of this harmony is inseparable from the presence of religious figures who are leaders and mobilizers of society. For the Toba Batak community, a leader is a person who is liked and emulated. The leader has a leadership charisma that functions as a singer and unifier, so that he becomes someone who is emulated, respected and obeyed. The low participation of the congregation in Church services and the minimum attendance of the congregation in participating in worship activities are a challenge to the existence of the Church. The Church as a social organization needs leaders who are capable, reliable and who are role models so that the Church can develop properly. The method used in this research is descriptive method with a qualitative approach. Data were collected by observation, interviews, document study and focus group discussion (FGD). The unit of analysis and informants is the community in the North Tapanuli Bahagian area. Data interpreted using field notes. Keywords :Charism, Leadership, Church Development